Identifying effective interventions to promote consumption of protein-rich foods from lower ecological footprint sources: A systematic literature review. - Rimante Ronto; Golsa Saberi; Gianna Maxi Leila Robbers; Stephanie Godrich; Mark Lawrence; Shawn Somerset; Jessica Fanzo; Josephine Y Chau (Public Library of Science (PLoS), 2022)
Addressing overconsumption of protein-rich foods from high ecological footprint sources can have positive impacts on health such as reduction of non-communicable disease risk and protecting the natural environment. With the increased attention towards development of ecologically sustainable diets, this systematic review aimed to critically review literature on effectiveness of those interventions aiming to promote protein-rich foods from lower ecological footprint sources. Five electronic databases (Medline, Web of Science, Scopus, Embase and Global Health) were searched for articles published up to January 2021. Quantitative studies were eligible for inclusion if they reported on actual or intended consumption of protein-rich animal-derived and/or plant-based foods; purchase, or selection of meat/plant-based diet in real or virtual environments. We assessed 140 full-text articles for eligibility of which 51 were included in this review. The results were narratively synthesised. Included studies were categorised into individual level behaviour change interventions (n = 33) which included education, counselling and self-monitoring, and micro-environmental/structural behaviour change interventions (n = 18) which included menu manipulation, choice architecture and multicomponent approaches. Half of individual level interventions (52%) aimed to reduce red/processed meat intake among people with current/past chronic conditions which reduced meat intake in the short term. The majority of micro-environmental studies focused on increasing plant-based diet in dining facilities, leading to positive dietary changes. These findings point to a clear gap in the current evidence base for interventions that promote plant-based diet in the general population.